Comparative Analysis of Financial Performance of Syariah and Conventional Banks: A Review from Statistics - Khalida, Khairunnisa; Riska, Maulia; Ajianing, Nyak Angeli; Nurhasanah, Nurhasanah (Majapahit Journal of Islamic Finance and Management, 2025)
Banking is an institution that has a significant impact on the real sector. The current banking system consists of different profit-sharing and interest-based systems, known in Islamic and conventional banks. Banking performance is an indicator of a country's economic performance. The financial performance of a bank or company can also be interpreted as a series of analyses conducted by the company to review the bank's compliance.Statistics makes a significant contribution to financial performance analysis. A statistical approach allows financial data to be processed objectively and generate reliable conclusions. The objective of this research is to analyze and compare the financial performance of Islamic banks and conventional banks in Indonesia.using a statistical science approach with indicators of Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin/Net Operating Margin (NIM/NOM).From the results of the analysis it is shown thatThere are significant differences in key profitability indicators (ROA and ROE) between conventional and Islamic banks, as confirmed by statistical hypothesis testing. This may be due to differences in business models, risk management, and investment strategies between the two banking systems.